Valuation for mergers, buyouts, and restructuring - Arzac, Enrique R. (Hoboken, NJ : J. Wiley, 2005)
The book provides insight into the theory behind core valuation, LBO's, and options pricing, which creates the foundation for mergers, buyouts and restructuring.
The accompanying CD-Rom contains Excel spreadsheets, calculators, and DealModeler (version 1), an integrated financial modeling Excel workbook.
Includes bibliographical references (p. R-1 to R-11) and index.
rua 26/02/15
Loans
System requirements for accompanying CD-ROM: Windows 98/00/NT and Macintosh.
Keywords: Corporations -- Valuation -- Textbooks; Consolidation and merger of corporations -- Textbooks